A learning paradigm for motion control of mobile manipulators - Abdessemed, Foudil; Monacelli, Eric; Benmahammed, Khier (Zielona Góra: Uniwersytet Zielonogórski)
Motion control of a mobile manipulator is discussed. The objective is to allow the end-effector to track a given trajectory in a fixed world frame. The motion of the platform and that of the manipulator are coordinated by a neural network which is a kind of graph designed from the kinematic model of the system.
Keywords: mobile manipulator; neural networks; backpropagation; obstacle avoidance